Water Scarce Cities : Thriving in a Finite World - World Bank (World Bank, Washington, DC, 2018)
Water scarce cities face unprecedented challenges: rapid urbanization and growth have put pressure on dwindling resources, and cities are further stressed by climate change and conflict shocks. Most operate under unsustainable water management practices, based on linear, engineering-based approaches, yet government planners and others are unaware how this situation could lead to major water shortages. This report, using information from the Water Scarce Cities Initiative, attempts to compile innovative approaches—based on cities' successful responses to water scarcity—to inspire a new kind of urban water security. The Water Scarce Cities report intends to magnify the successes of those urban areas and to stimulate knowledge exchange between global cities, their policy makers and, most important, the practitioners. It first seeks to shift predominant, outdated, mostly linear, and siloed thought patterns that sometimes lead to disjointed and costly investment decisions without necessarily providing protection against depleting resources or an increasingly adversarial climate. It then demystifies innovative urban water practices, including managing conventional resources such as aquifers more effectively, tapping new and nonconventional resources such as wastewater, con-trolling demand, or engaging differently (such as showing how the practices were done and what can be learned from them). The goal is to engage meaningfully with diverse water scarce cities to facilitate concrete engagement, product development, and technical assistance.